Propuesta de reforma a la Ley Orgánica de defensa del consumidor en relación a la inserción de la figura jurídica: consumidor expuestos o bystander - Santana Villegas, Darwin Vinicio (2017)
The purpose of this paper is to analyze consumer law in its capacity as an exposed consumer, with the general objective of: Reform of the Organic Law of Consumer Defense in relation to the inclusion of the third party exposed for legal protection, because these people they are exposed to damages that are caused by products or services that have been acquired by another person, which the law calls consumers, but that due to material or accidental damage attributable to the quality of the product or service causes damage that must be compensated, but because this figure is not regulated within the legal framework, it is difficult and even impossible in many cases to obtain reparation or compensation for this exposed third party affected by poor quality. Therefore, in the present investigation, we intend to analyze and compare international legislation in reference to the present figure of the third party that has been inserted in the Argentine, Brazilian and United States regulations, in order to propose the feasibility of inserting this legal figure of protection and protection for those persons who, without being part of the consumer relationship, suffer physical or material damages due to the exposure to the product and who are entitled to demand reparation or indemnification, based on constitutional and mercantile principles that require the supplier or the manufacturer to guarantee the quality and safety of the product that it sends to the market…..